The Development of Arabic Linguistics in Educational Studies: An Analysis of Ibn Khaldun's Thought - Febrina Dwi Cahyani; Mazi Septina Mirantika (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The study of Arabic linguistics plays a central role in the development of education, especially in efforts to systematically improve the quality of Arabic language learning and to be responsive to learners' needs. The development of Arabic linguistics not only covers aspects of language such as phonology, morphology, syntax, and semantics, but is also closely related to contextual and learner-needs-based educational approaches. Ibn Khaldun, as an Islamic thinker, made a major contribution to the development of linguistics, especially through his ideas in the Muqaddimah. This study aims to examine the relevance of Ibn Khaldun's ideas to the development of Arabic linguistics and their application in education. The research method used is a Systematic Literature Review (SLR), which involves collecting relevant literature and journals. The analysis indicates that Ibn Khaldun emphasized the importance of gradual learning methods (tadarruj), repetition (takrir), discussion (munazarah), and learning through comparative studies (rihlah). His thoughts emphasize that Arabic not only functions as a means of communication but also as an instrument of intellectual formation and cultural identity. Therefore, Ibn Khaldun's ideas are highly relevant to formulating effective Arabic teaching strategies that align with the dynamics of the times.